Transformasi Digital Menuju Responsive Website Menggunakan Content Management System - Maryam; Dian Purworini; Rona Rizky Bunga Chasanah; Widi Widayat; Diah Priyawati (AI Society & STMIK Indonesia, 2025)
In the digital era, organizations are expected to follow with technological advancements, including the need to provide informative and engaging users.. This study aims to describe the transformation of a da'wah organization in delivering information as part of a broader digital outreach strategy. The main focus to utilize the WordPress CMS as a solution to enhance website responsiveness and user reach. A practical approach was adopted through the Web Development Life Cycle method, starting from analysis requirements to technological implementation. Key aspects considered include responsive design, content integration, and user experience. Functionality testing using the black-box method confirmed that the system performs as expected. The results demonstrate improved content accessibility, optimal website responsiveness across devices, and increased user engagement. This system can serve as a model for other organizations seeking to adopt similar technologies to expand the da'wah.